Peran Mahasiswa Kampus Mengajar Dalam Meningkatkan Pengetahuan Literasi Numerasi Hingga Teknologi Siswa SMP PGRI 5 Taman Sidoarjo - Linda Novia Sari; Cholis Hidayati (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
The Teaching Campus Program is a form of implementing Merdeka Belajar Kampus Merdeka (MBKM) in the form of teaching assistance to empower students to assist the school learning process in various villages / cities, one of which is PGRI 5 Taman Junior High School, Sidoajo, East Java. In this program, the students involved have the responsibility of assisting the school in the teaching process, helping with technology adaptation, and helping with school administration. The purpose of this research is to find out how the work of students in improving numeracy literacy to technological adaptation at SMP PGRI 5 Taman. The data collection technique used is the interview technique. The results of this program are an increase in the knowledge of PGRI 5 Taman Junior High School students in terms of numeracy literacy to technological adaptation.